Socially responsible investment indices in Asian markets : merging stakeholder theories with social construction for improved index construction methodology - Ho, Ching-ching, Mary (The University of Hong Kong (Pokfulam, Hong Kong), 2014)
The growth of the managed investment industry brings with it the potential for institutional investors to exert their influence on boards of listed companies to deliver strong and sustainable growth. The concepts of socially responsible investment (SRI), responsible investment (RI) or ethical investment (EI) have become part of mainstream investment practices in many financial markets. While SRI is largely a qualitative concept, its survival and adoption by the mainstream investment community may, in part, be due to the formalising of its concepts into language that investors, asset managers and analysts can more readily understand: the benchmark index.